ChemInform Abstract: Synthesis and Systematic Trends in Structure and Electrical Properties of [(SnSe)1.15]m(VSe2)1, m = 1, 2, 3, and 4. Issue 29 (22nd July 2014) - Atkins, Ryan; Dolgos, Michelle; Fiedler, Andreas; Grosse, Corinna; Fischer, Saskia F.; Rudin, Sven P.; Johnson, David C.
Abstract The title compounds are synthesized by physical vapor deposition of subnanometer elemental layers followed by annealing under a nitrogen atmosphere leading to self‐assembly of the precursors into the desired [(SnSe)1.15]m(VSe2) (m = 1, 2, 3, and 4) intergrowth products.